Impact of suggestion on the human experimental model of cold hyperalgesia after topical application of high‐concentration menthol [40%]. (11th June 2018) - Helfert, S.; Reimer, M.; Barnscheid, L.; Hüllemann, P.; Rengelshausen, J.; Keller, T.; Baron, R.; Binder, A.
Abstract: Background: Human experimental pain models in healthy subjects offer unique possibilities to study mechanisms of pain within a defined setting of expected pain symptoms, signs and mechanisms. Previous trials in healthy subjects demonstrated that topical application of 40% menthol is suitable to induce cold hyperalgesia. The objective of this study was to evaluate the impact of suggestion on this experimental human pain model. Methods: The study was performed within a single‐centre, randomized, placebo‐controlled, double‐blind, two‐period crossover trial in a cohort of 16 healthy subjects. Subjects were tested twice after topical menthol application (40% dissolved in ethanol) and twice after ethanol (as placebo) application. In the style of a balanced placebo trial design, the subjects received during half of the testing the correct information about the applied substance (topical menthol or ethanol) and during half of the testing the incorrect information, leading to four tested conditions (treatment conditions: menthol‐told‐menthol and menthol‐told‐ethanol ; placebo conditions: ethanol‐told‐menthol and ethanol‐told‐ethanol ). Results: Cold but not mechanical hyperalgesia was reliably induced by the model. The cold pain threshold decreased in both treatment conditions regardless whether true or false information was given. Minor suggestion effects were found in subjects with prior ethanol application. Conclusions: The menthol model is a reliable, nonsuggestible model to induce cold hyperalgesia. Mechanical hyperalgesia is not as reliable to induce. Significance: Cold hyperalgesia may be investigated under unbiased and suggestion‐free conditions using the menthol model of pain.